FEATURES OF STUDENT LEARNING MOTIVATION - Surayyo Umirzoqova Xudoyberdiyevna (Web of Journals Publishing, 2024)
The article describes the approaches to examining educational motivation, modern challenges, and issues related to learning motivation, and outlines the quantitative and qualitative indicators of educational quality.
Keywords: educational motivation, quantitative and qualitative indicators, international research, digital technologies.